CHARACTER OF SEDIMENTATION IN LAKE BAIKAL IN THE HOLOCENE - Vologina E.G.; Sturm M.; Vorob'eva S.S.; Granina L.Z.; Toshchakov S.Yu. (My University, 2003)
The bottom sediments of Lake Baikal were studied, with the emphasis placed upon the conditions of sedimentation in the Holocene and material composition of sediments. On the basis of study of spatial distribution of sediments in all parts of the lake, six characteristic zones of sedimentation have been recognized. Lithological types of sections of the modern bottom deposits of Baikal are described in detail. Much attention is given to the description of turbidite sedimentation as one of the main mechanisms of formation of bottom sediments in the Holocene. The features that distinguish turbidites from sediments accumulated under calm conditions are shown. It has been established that buried relics of oxidized Fe-Mn-formations occur not only in the northern basin of the lake but also in the southern basin.
Keywords: Bottom sediments; sedimentation conditions; turbidites; frustules; oxidized layers; Baikal; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен